The first report of polymorphisms of the prion protein gene (PRNP) in Pekin ducks (Anas platyrhynchos domestica) - Jeong, Min-Ju; Wang, Zerui; Zou, Wen-Quan; Kim, Yong-Chan; Jeong, Byung-Hoon (Frontiers in Veterinary Science, 2023)
Background: Prion diseases have been extensively reported in various mammalian species and are caused by a pathogenic prion protein (PrP Sc ), which is a misfolded version of cellular prion protein (PrP C ). Notably, no cases of prion disease have been reported in birds. Single nucleotide polymorphisms (SNPs) of the prion protein gene (PRNP) that encodes PrP have been associated with susceptibility to prion diseases in several species. However, no studies on PRNP polymorphisms in domestic ducks have been reported thus far.To investigate PRNP polymorphisms in domestic ducks, we isolated genomic DNA from 214 Pekin duck samples and sequenced the coding region of the Pekin duck PRNP gene.We analyzed genotype, allele, and haplotype distributions and linkage disequilibrium (LD) among the SNPs of the Pekin duck PRNP gene. In addition, we evaluated the effects of the lone non-synonymous SNP on the function and structure of PrP using the PROVEAN, PANTHER, SNPs & GO, SODA, and AMYCO in silico prediction programs.We found five novel SNPs, c.441T>C, c.495T>C, c.582A>G, c.710C>T(P237L), and c.729C>T, in the ORF region of the PRNP gene in 214 Pekin duck samples. We observed strong LD between c.441T>C and c.582A>G (0.479), and interestingly, the link between c.495T>C and c.729C>T was in perfect LD, with an r 2 value of 1.0. In addition, we identified the five major haplotype frequencies: TTACC, CTGCC, CTACC, CCGCT, and CTATC. Furthermore, we found that the non-synonymous SNP, c.710C>T (P237L), had no detrimental effects on the function or structure of Pekin duck PrP. However, the non-synonymous SNP had deleterious effects on the aggregation propensity and solubility of Pekin duck PrP compared with wildtype Pekin duck PrP. 4 Conclusion: To the best of our knowledge, this study is the first report on the genetic 47 characteristics of PRNP SNPs in Pekin ducks.